TOWARDS PLURI-PERSPECTIVISM BIOETHICS - Đurđić, Vojislav; Trajković, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Why are we lawyers still dealing with Bioethics? Who has given us the opportunity to, out of our own self-sufficiency, which legal doctrine and practice have enabled, make a journey towards the field of Bioethics? The separation of the law from Bioethics, understood as Pluri-Perspectivistic field of action of a wide range of science and teaching, leaves the law isolated and limited to its own frames that become insufficient for the development of the legal thought. This causes an irreparable damage to the law, as well as to Bioethics which does not get legal solutions to its problems, which is necessary. Since Bioethics is not a mere presentation of views, comprehending the problem, but also their reflexion and, eventually, their standardization, i.e. the providing of legal answers to the social issues that arise from the field of Bioethics. Thus, not only the theory and philosophy of law find their place in the field of Bioethics, but the same goes for the theory of criminal law, which, also, even in the practical sphere of jurisprudence, is most likely to protect the life. Such a non-isolation of jurisprudence enables it to step out of its own constrains and accept the "Bioethical sensibility." This is possible only if we recognize the Pluri-Perspectivism as a starting point in both Bioethics and the law. Is it possible that the law be understood as a field of activity of the various value orientations? Pluri-Perspectivism, which does not go into relativism, will claim that it is possible, and we are inclined to believe it, given the proper results obtained in the field of Bioethics via such a postulate.
Keywords: pluri-perspectivism; integralism; criminal-law theory; law; bioethics; ethics